2006
DOI: 10.1124/jpet.106.102129
|View full text |Cite
|
Sign up to set email alerts
|

Nitroglycerin Attenuates Human Endothelial Progenitor Cell Differentiation, Function, and Survival

Abstract: Endothelial progenitor cells (EPCs) participate in angiogenesis and the response to chronic ischemia. Risk factors and cardiovascular disease attenuate EPC number, function, and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 39 publications
2
16
0
3
Order By: Relevance
“…In a small clinical trial NTG treatment of healthy volunteers increased circulating CD34 progenitor cells, but also enhanced susceptibility of expanded EPCs to apoptosis. 45 Ex vivo NTG exposure increased apoptosis and decreased phenotypic differentiation of EPCs. 45 In the present study, we demonstrate therapy with two different long-acting nitrates to increase levels of circulating EPCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a small clinical trial NTG treatment of healthy volunteers increased circulating CD34 progenitor cells, but also enhanced susceptibility of expanded EPCs to apoptosis. 45 Ex vivo NTG exposure increased apoptosis and decreased phenotypic differentiation of EPCs. 45 In the present study, we demonstrate therapy with two different long-acting nitrates to increase levels of circulating EPCs.…”
Section: Discussionmentioning
confidence: 99%
“…45 Ex vivo NTG exposure increased apoptosis and decreased phenotypic differentiation of EPCs. 45 In the present study, we demonstrate therapy with two different long-acting nitrates to increase levels of circulating EPCs. However, functionally there were strong differences between the tested nitrates.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 This represents a potentially important source of "high-output" NO production that may be associated with oxidative stress and the production of reactive NO species that attenuate the mobilization, function, and survival of EPCs. 29,30 Increasing evidence indicates that inflammation has a key role in the pathogenesis of PAH. As in earlier studies, [31][32][33] we found evidence of chronic inflammation with raised plasma levels of the inflammatory mediators TNF-␣, IL-6, and CCL-2.…”
Section: Discussionmentioning
confidence: 99%
“…Among factors involved in reducing the bioavailability of NO, recent work reported by researchers confirm that the development of tolerance to nitrates is associated with increased oxidative stress (Oelze et al, 2010;DiFabio et al, 2006;Muller et al, 2004;Parker, 2004;Gori et al, 2001;Laight et al, 1997Laight et al, , 1998. In addition, a key enzyme involvement of nitroglycerin and nitrates biotransformation, namely the mitochondrial aldehyde dehydrogenase (ALDH 2), is inhibited by reactive oxygen species (ROS) which in addition, can degrade nitric oxide (Wenzel et al, , 2009bDaiber et al, 2004Daiber et al, , 2009bSydow et al, 2004).…”
Section: Discussionmentioning
confidence: 99%